2019
DOI: 10.1080/19475683.2019.1702099
|View full text |Cite
|
Sign up to set email alerts
|

Why public health needs GIS: a methodological overview

Abstract: The short paper provides an overview on how geographic issues have become increasingly relevant to public health research and policy, particularly through the lens of geographic information systems (GIS). It covers six themes with an emphasis on methodological issues. (1) Our health-related behaviour varies across geographic settings, so should public health policy. (2) Facilities (supply) and patients (demand) in a health-care market interact with each other across geopolitical borders, and measures of health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(104 citation statements)
references
References 45 publications
1
97
0
6
Order By: Relevance
“…Furthermore, this study only split Arizona into three regions (ie, central, northern, and southern) rather than examining prediction accuracy at both the state and county level. In fact, there may be geospatial differences in population mobility due to the plausible differential implementation fidelity of NPIs and reactions to reopening policies by county [ 20 , 21 ]. Additionally, there may be geospatial differences in the estimation of population mobility on social media as the number of users and their demographic characteristics may differ by county.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this study only split Arizona into three regions (ie, central, northern, and southern) rather than examining prediction accuracy at both the state and county level. In fact, there may be geospatial differences in population mobility due to the plausible differential implementation fidelity of NPIs and reactions to reopening policies by county [ 20 , 21 ]. Additionally, there may be geospatial differences in the estimation of population mobility on social media as the number of users and their demographic characteristics may differ by county.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the increased abundance of Culex pipiens and C. restuans in NENA forests has led to increased transmission of West Nile Virus to wildlife such as the ruffed grouse (Bonasa umbellus) [7]. The increase in mosquitoes and risk of disease transmission [8] requires a thorough understanding of the environmental variables regulating these disease vectors.…”
Section: Introductionmentioning
confidence: 99%
“…As a one-size-fits-all policy rarely serves as an effective strategy to be adopted in large countries like China [ 57 ], it is highly recommended that geospatial heterogeneity be considered throughout policy-making procedures at regional levels in order to facilitate the formulation and implementation of region-specific strategies for optimization purposes. In order to achieve such region-specific optimization, it is highly recommended that experts from interdisciplinary backgrounds are extensively engaged in policy-making procedures for various healthcare settings as part of the healthcare reform, including public health professionals, health and medical geographers, geographic information science (GIS) practitioners, environmentalists, and spatial statisticians [ 63 , 64 ]. More importantly, the adoption of an innovatively developed Bayesian-based local spatiotemporal regression STVC model in our study demonstrated great value in the spatiotemporal analysis of various influencing factors in the field of public health, which could be further extended for adoption in broader areas such as environment and earth sciences.…”
Section: Discussionmentioning
confidence: 99%